2022
DOI: 10.1111/ijfs.15656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size in wasted bread flour properties

Abstract: Bread is wasted at different stages in the food value chain, mainly in industry and retail markets. Wasted bread can be milled into flour to be used in the elaboration of other food products. Milling can generate flours with different particle sizes that influence their properties. This study analysed the effect of particle size (200, 500 and 1000 μm) on the hydration, pasting and gel properties of flours elaborated with four different stale breads. Bread flours show a higher cold water absorption capacity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(71 reference statements)
1
2
0
Order By: Relevance
“…There was no significant difference between extrudates from flours with 40%, 30%, and 20% moisture content whereas the control and extrudates from flour at 10% moisture content exhibited a significant difference. This means that gelatinized starches have a lower capacity for oil absorption; a similar observation was reported by Guerra-Oliveira et al (2022). A lower range (80-108) of oil absorption was reported by (Kacou et al, 2018) for seven different cassava varieties.…”
Section: Oil Absorption Capacitysupporting
confidence: 77%
See 1 more Smart Citation
“…There was no significant difference between extrudates from flours with 40%, 30%, and 20% moisture content whereas the control and extrudates from flour at 10% moisture content exhibited a significant difference. This means that gelatinized starches have a lower capacity for oil absorption; a similar observation was reported by Guerra-Oliveira et al (2022). A lower range (80-108) of oil absorption was reported by (Kacou et al, 2018) for seven different cassava varieties.…”
Section: Oil Absorption Capacitysupporting
confidence: 77%
“…It was also observed that WAI and OAC had a negative relationship. This is because flours with smaller particle sizes can easily absorb water, while flours with high water absorption have a lower capacity for oil absorption (Guerra-Oliveira et al, 2022).…”
Section: Principle Component Analysismentioning
confidence: 99%
“…The use of flour obtained from dried bread in baking has been studied earlier [ 10 , 11 , 55 ], but those studies focused on obtaining light-colored bread. It was found that with the increase in the share of dried bread, in general, worse quality characteristics (lower volume, worse texture) and, above all, a deterioration in the color of the product were obtained.…”
Section: Resultsmentioning
confidence: 99%